PROMOSI PERPUSTAKAAN MELALUI VIDEOBLOGGING (VLOGGING) - Sely Yoanda (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
The development of information technology causes information easily accessible, so the function of the library as a vehicle of information becomes less desirable and cause the interest of visitors to the library to be reduced. The library needs to do library promotion by utilizing information technology that is through video blogging (vlogging). The library promotion process through vlogging should be done with good concept and planning by the librarian. The purpose of library promotion through video blogging (vlogging) is to increase the interest of visitors to libraries, improve the library's image in the community, promote the existence of library science department, and introduce to the public that the work of the librarian is not just a book keeper.